A Century-Old Mystery Unveiled: Sekizaisou is a Natural Lignin Mutant. Issue 4 (12th February 2020) - Yamamoto, Masanobu; Tomiyama, Hirokazu; Koyama, Akio; Okuizumi, Hisato; Liu, Sarah; Vanholme, Ruben; Goeminne, Geert; Hirai, Yuta; Shi, Hu; ,; Takata, Naoki; Ikeda, Tsutomu; et al.
Abstract : Sekizaisou, a red-wood mulberry variety used in traditional sericulture, is a naturally occurring lignin mutant.